PENENTUAN KONDISI OPTIMUM PENGADUKAN DALAM PROSES KOAGULASI - Tantri Mayang Arum (Purifikasi, 2004)
This research was done at turbidity level of of 160 NTU. The research was done with jar test by varying the number of blade (2, 4 and 6 blades), diameter of the padle (55%, 65% and 75% of tank diameter), rotation speed of 190 rpm, 200 rpm and 210 rpm and distance of the padle to the tank base of ½, ¾ and 1 times of paddle diameter. This research concluded that those four factors influenced mixing physical factor equal to 90%. The main factor which affected turbidity removal were the number of the blade (46,7%) followed by the diameter of the padle (26,1%), the speed of mixing rotation (17,4%) and the distance of padle to the tank base (9,8%). Optimum condition reached by the condition of mixing using combination of 6 blades with padle’s diameter 75% to tank width, speed rotation of 210 rpm and distance of padle to tank base of ½ of the paddle diameter.